The Impact of Environmental Law on the Development of the City of Manado, Indonesia - KALALO, Flora Pricilla (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020DO - 10.14505//jarle.v11.1(47).10, 2020)
The environmental laws provide protection, good management, and conservation for the nature. The enforcement of said law does not mean stopping or negating development activities in the area. Progress must go on in accordance to agreed-upon development programs. Such developments, which in this case take place in Manado, need to take into account the impact towards the environment, in accordance to Environmental Protection and Management Act No. 32 of 2009 so as to not contaminate or compromise the life-supporting nature, both short-term and long term. For that purpose, developments in Manado must be executed with respect to sustainable, environmentally friendly development concepts, so development and natural conservation efforts can progress alongside each other.